1995
DOI: 10.1111/j.1476-5381.1995.tb15070.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by halothane of potassium‐stimulated acetylcholine release from rat cortical slices

Abstract: 1 Cholinergic neurones in the basal forebrain are linked to cortical activation and arousal. 2 The present study was designed to examine the hypothesis that clinically relevant doses of halothane (0.1 to 5%) would significantly reduce depolarization-evoked acetylcholine (ACh) release from rat cortical slices. 3 ACh release was measured from rat cortical slices by a chemiluminescent technique. 4 Depolarization-evoked ACh release was inhibited significantly by halothane with an IC50 of 0.38%. This value equates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Although this apparent discrepancy could be explained by the halothane dose used, tissue and methodological differences should also be taken into account. Moreover, it is worth noting that, as in the present study, Griffiths et al . (1995) reported a trend to an increase in the release of ACh in brain cortical slices from unstimulated samples at all concentrations of halothane tested (0.037–1.19 m M ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Although this apparent discrepancy could be explained by the halothane dose used, tissue and methodological differences should also be taken into account. Moreover, it is worth noting that, as in the present study, Griffiths et al . (1995) reported a trend to an increase in the release of ACh in brain cortical slices from unstimulated samples at all concentrations of halothane tested (0.037–1.19 m M ).…”
Section: Discussionsupporting
confidence: 75%
“…There are few studies of the effect of volatile general anaesthetics on the release of ACh. In some of these studies, halothane was shown to decrease potassium‐evoked ACh release from rat cortical synaptosomes ( Johnson & Hartzell, 1985 ) and rat cortical slices ( Griffiths et al ., 1995 ). In contrast, no effect on potassium‐stimulated ACh release was observed in rat cerebral cortex in the presence of 1.25% halothane, 3% enflurane or 0.2% methoxyflurane ( Bazil & Minneman, 1989a , 1989b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same result was observed with halothane on pontine ACh release (Keifer et al, 1994). In addition, it was shown that halothane decreases the potassium-evoked ACh release from rat cortical synaptosomes (Johnson and Hartzell, 1985) and rat cortical slices (Griffiths et al, 1995).…”
Section: Discussionmentioning
confidence: 51%
“…Although there have been some reports of the action of volatile anesthetics on ACh release, it is not clear as to how these drugs alter the release of this transmitter. It was shown that volatile anesthetics decreased the release of ACh in in vitro (Griffiths et al, 1995;Johnson and Hartzell, 1985) and in in vivo systems (Keifer et al, 1994;Shichino et al, 1997;Shichino et al, 1998). However, other studies reported an increase in the release of ACh by halothane (Gomez et al, 1999) and isoflurane from rat brain cortical slices (Gomez et al, 2000), and by halothane in rat striatal slices (Adachi et al, 2001).…”
Section: Introductionmentioning
confidence: 93%